Desain dan Rancang Bangun Aplikasi Laporan KKN Berbasis Laravel dengan Visual Studio dan Database - safutri, lisa; Maiyana, Efmi (Universitas Aisyah Pringsewu, 2025)
Community Service Program (KKN) is an academic activity that must be undertaken by university students as a form of community engagement. In practice, the reporting process for KKN activities is often carried out manually, which is inefficient and prone to data loss. This research aims to design and develop a web-based KKN reporting application using the Laravel framework, supported by Visual Studio Code as the code editor and MySQL as the database management system. The method used is Research and Development (R&D), which includes literature study, requirement analysis, system design, development, and application testing. The result of this research is a web-based application that enables students to create and upload activity reports, and allows supervisors to provide assessments directly through the system. The application is tested based on functionality, user interface (UI/UX), and performance. This system is proven to improve efficiency, transparency, and accuracy in the KKN reporting process, while also simplifying monitoring for lecturers and administrators.